Inconsistent Cognitive Assessment Criteria in PD-MCI Research [Letter] - Wang J (Neuropsychiatric Disease and Treatment)
Jiawen Wang Hanzhong People’s Hospital, Hanzhong City, Shaanxi Province, 723000, People’s Republic of ChinaCorrespondence: Jiawen Wang, Hanzhong People’s Hospital, 251 North Tuanjie Street, Hantai District, Hanzhong City, Shaanxi Province, 723000, People’s Republic of China, Email 393632929@qq.com